Acute Precipitants of Physical Elder Abuse: Qualitative Analysis of Legal Records From Highly Adjudicated Cases. Issue 12 (June 2019) - Rosen, Tony; Bloemen, Elizabeth M.; LoFaso, Veronica M.; Clark, Sunday; Flomenbaum, Neal E.; Breckman, Risa; Markarian, Arlene; Riffin, Catherine; Lachs, Mark S.; Pillemer, Karl
Elder abuse is a common phenomenon with potentially devastating consequences for older adults. Although researchers have begun to identify predisposing risk factors for elder abuse victims and abusers, little is known about the acute precipitants that lead to escalation to physical violence. We analyzed legal records from highly adjudicated cases to describe these acute precipitants for physical elder abuse. In collaboration with a large, urban district attorney's office, we qualitatively evaluated legal records from 87 successfully prosecuted physical elder abuse cases from 2003 to 2015. We transcribed and analyzed narratives of the events surrounding physical abuse within victim statements, police reports, and prosecutor records. We identified major themes using content analysis. We identified 10 categories of acute precipitants that commonly triggered physical elder abuse, including victim attempting to prevent the abuser from entering or demanding that he or she leave, victim threatening or attempting to leave/escape, threat or perception that the victim would involve the authorities, conflict about a romantic relationship, presence during/intervention in ongoing family violence, issues in multi-generational child rearing, conflict about the abuser's substance abuse, confrontation about financial exploitation, dispute over theft/destruction of property, and disputes over minor household issues. Common acute precipitants of physical elder abuse may be identified. Improved understanding of these acute precipitants for escalation to physical violence and their contribution to elder abuse may assist in the development of prevention and management strategies.